2008
DOI: 10.1088/0022-3727/41/19/195206
|View full text |Cite
|
Sign up to set email alerts
|

Ozone generation by negative corona discharge: the effect of Joule heating

Abstract: Ozone generation in pure oxygen using a wire-to-cylinder corona discharge reactor is experimentally and numerically investigated. Ozone concentration is determined by means of direct UV spectroscopy and the effects of Joule heating and ozone decomposition on the electrodes are analysed for different discharge gaps. The numerical model combines the physical processes in the corona discharge with the chemistry of ozone formation and destruction. The chemical kinetics model and the electrical model are coupled th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 17 publications
3
22
1
Order By: Relevance
“…Eliasson [14] employed 16 species and 70 reactions in his model and demonstrated that the excited species are essential in ozone production using a parallelplate DBD system. Yanallah [15] adopted 15 species and 38 reactions without ioneion recombination reactions to investigate the negative corona discharge in a wire-cylinder reactor. Moreover, only 4 species and 5 reactions were included in Loiseau's model to simulate the axial and radial distributions of ozone in a cylindrical ozonizer [16].…”
Section: Computational Domain and Chemistrymentioning
confidence: 99%
“…Eliasson [14] employed 16 species and 70 reactions in his model and demonstrated that the excited species are essential in ozone production using a parallelplate DBD system. Yanallah [15] adopted 15 species and 38 reactions without ioneion recombination reactions to investigate the negative corona discharge in a wire-cylinder reactor. Moreover, only 4 species and 5 reactions were included in Loiseau's model to simulate the axial and radial distributions of ozone in a cylindrical ozonizer [16].…”
Section: Computational Domain and Chemistrymentioning
confidence: 99%
“…5b). The structure of the electrical discharge is almost identical to the case of zero-flow rate [8], that is, the inter-electrode space appears divided in three regions: the ionization region, around of the cathode; the active region, where the electron density is maximum; and drift region, where the negative space charge accumulates. The transport of charge in the drift region is entirely due to O 2 − and O 3 − .…”
Section: Resultsmentioning
confidence: 97%
“…The experimental set-up is similar to the one used in previous works [8,9]. The corona discharge reactor consists of a smooth tungsten wire, with radius r 0 = 0.05 mm, placed along the axis of a stainless steel cylinder.…”
Section: Experimental Set-upmentioning
confidence: 99%
See 2 more Smart Citations